Risk Models for Advanced Melanoma Patients Under Anti-PD-1 Monotherapy—Ad hoc Analyses of Pooled Data From Two Clinical Trials - Bai, Xue; Dai, Jie; Li, Caili; Cui, Chuanliang; Mao, Lili; Wei, Xiaoting; Sheng, Xinan; Chi, Zhihong; Yan, Xieqiao; Tang, Bixia; Lian, Bin; Wang, Xuan; et al. (Frontiers in Oncology, 2021)
BACKGROUND The best response and survival outcomes between advanced melanoma patients treated with anti-PD-1 monotherapy vary greatly, rendering a risk model in need to optimally stratify patients based on their likelihood to benefit. METHODS We performed an ad hoc analysis of 89 advanced melanoma patients treated with anti-PD-1 monotherapy from two prospective clinical trials at Peking University Cancer Hospital from Apr 2016 to May 2018. Clinicodemographical characteristics, baseline and early-on-treatment (median 0.6 months after anti-PD-1 monotherapy initiation) routine laboratory variables, including complete blood count and general chemistry, and best response/survival data were extracted and analyzed in both univariate and multivariate logistic and Cox models. RESULTS After three rounds of screening, risk factors associated with poorer PFS included high pre-treatment neutrophil, derived neutrophil-lymphocyte ratio (dNLR), low pre-treatment hemoglobin, and low early-on-/pre-treatment fold-change of eosinophil; those with poorer OS included high pre-treatment neutrophil, eosinophil, PLT, early-on/pre-treatment fold-change of LDH and neutrophil; those with poorer best response included high pre-treatment NLR and early-on-/pre-treatment LDH fold-change. Risk models (scale: low, median-low, median high, and high risk) were established based on these risk factors as dichotomous variables and M stage, for PFS (HR 1.976, 95% CI, 1.507-2.592, P<.001), OS (HR 2.348, 95% CI, 1.688-3.266, P<.001), and non-responder (OR 3.586, 95% CI, 1.668-7.713, P=.001), respectively. For patients with low, median-low, median-high, and high risk of developing disease progression (PD), 6-month PFS rates were 64.3% (95% CI, 43.5-95.0%), 37.5% (95% CI, 22.4-62.9%), 9.1% (95% CI, 3.1-26.7%), and 0%, respectively. For patients with OS risks of low, median-low, median-high, and high, OS rates at 12 months were 82.5% (95% CI, 63.1-100), 76.6% (95% CI, 58.4-100%), 42.1% (95% CI, 26.3-67.3%), and 23.9% (95% CI, 11.1-51.3%), respectively. For patients with risks of low, median-low, median-high, and high of being a non-responder, objective response rates were 50.0% (95% CI, 15.7-84.3%), 27.8% (95% CI, 9.7-53.5%), 10.3% (95% CI, 2.9-24.2%) and 0%, respectively. CONCLUSION A risk scoring model based on clinicodemographical characteristics and easily obtainable routinely tested laboratory biomarkers may facilitate best response and survival outcome predication and personalized therapeutic decision making for anti-PD-1 monotherapy treated advanced melanoma patients in Asia.